The Basic Categories and Assumptions for Contemporary Chinese Argumentation Studies - Qiang, Zhou (Sinología hispánica. China Studies Review, 2016)
A systemic study of argumentation in definition, stages, types, techniques, and principles of argumentation has been reflected. Based on this reflection, the basic assumptions of contemporary Chinese argumentation studies have been drawn upon. Finally, the underlying reasons for the present situation have been analyzed.